Media rhetoric and social responsibility in Nigeria (2009)
The essential feature of modern mass media is its large, heterogeneous and widely dispersed audience. This feature has its root in the audience of the traditional theatre, musical performances and political rallies, which involves physical gathering of people previously sharing little perspectives about the events bringing them together. Rhetorical styles are strong instruments of sustaining the attention of people in such gatherings. Such styles sometimes involve evoking emotions and audience empathy to the cause of the speakers in such gatherings and often, this stimulates the audience into predictable actions. This feature is strongly shared by the modern mass media, whose immense strength to stimulate the masses into negative and positive actions have been recognized. Technological innovations in the media are constantly reinforcing this strength on the audience who are now bigger, much more dispersed and relying more on the media with pervasive consequences of media messages on their behavioral disposition towards public issues. This paper critically reviews the rhetorical influence of the mass media on Nigerian society and makes suggestions on ways by which the media could exhibit more social responsibility during their rhetorical transaction with the audience